Contemporary contestations over working time: time for health to weigh in - Dixon, J.; Carey, G.; Strazdins, L.; Banwell, C.; Woodman, D.; Burgess, John; Bittman, M.; Venn, D.; Sargent, G. (BioMed Central Ltd, 2014)
Non-communicable disease (NCD) incidence and prevalence is of central concern to most nations, along with international agencies such as the UN, OECD, IMF and World Bank. As a result, the search has begun for ‘causes of the cause’ behind health risks and behaviours responsible for the major NCDs. As part of this effort, researchers are turning their attention to charting the temporal nature of societal changes that might be associated with the rapid rise in NCDs. From this, the experience of time and its allocation are increasingly understood to be key individual and societal resources for health (7–9). The interdisciplinary study outlined in this paper will produce a systematic analysis of the behavioural health dimensions, or ‘health time economies’ (quantity and quality of time necessary for the practice of health behaviours), that have accompanied labour market transitions of the last 30 years - the period in which so many NCDs have risen sharply.